An Innovative Tool for Technical, Environmental and Economic Design of Building Energy Plants: A Case Study in Umbria. (December 2015) - Petrozzi, Alessandro; Coccia, Valentina; Cavalaglio, Gianluca; Nicolini, Andrea; Cotana, Franco
Abstract: The European goals on environmental sustainability and carbon footprint reduction should be reached by the installation of Renewable Energy Sources (RES) plants. However, the massive development of RES plants has inevitably caused new relevant problems and critical situations due to their low energy density, their social acceptance and the non-programmability of some sources. A smart tool is proposed to evaluate the integration feasibility of different energy plants; this tool is also able to estimate the environmental impacts caused by the several proposed plants for building energy production in terms of land usage, carbon footprint and water consumption. A case study, a rural tower shaped building in Umbria, is analyzed to validate the innovative tool: environmental, energy and economic parameters are calculated to allow the designer to define the best energy plant configuration.